2019
DOI: 10.1093/ecco-jcc/jjz153
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Microscopic Inflammation at Resection Margins on Early Postoperative Endoscopic Recurrence After Ileocaecal Resection for Crohn’s Disease

Abstract: Background and Aims The pathogenesis and risk factors for early postoperative endoscopic recurrence of Crohn’s disease [CD] remain unclear. Thus, this study aimed to identify whether histological inflammation at the resection margins after an ileocaecal resection influences endoscopic recurrence. Methods We have prospectively followed up patients with CD who underwent ileocaecal resection at our hospital between January 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 21 publications
0
54
2
5
Order By: Relevance
“…Different studies demonstrated a significantly increased risk for endoscopic recurrence following ileocecal resection in case of microscopic inflammation at the resection margins. Following ileocecal resection, Poredska et al showed that 56.5% of patients with positive resection margins suffered from endoscopic recurrence after six months in comparison to 4.8% with noninflamed resection margins (p < 0.001) [80]. Furthermore, another study from France confirmed an increased risk of clinical and surgical recurrence after resection in case of a positive histological margin.…”
Section: Improved Surgical Technique May Further Support the Beneficial Effects Of Surgery To Maintain Remission In CDmentioning
confidence: 99%
“…Different studies demonstrated a significantly increased risk for endoscopic recurrence following ileocecal resection in case of microscopic inflammation at the resection margins. Following ileocecal resection, Poredska et al showed that 56.5% of patients with positive resection margins suffered from endoscopic recurrence after six months in comparison to 4.8% with noninflamed resection margins (p < 0.001) [80]. Furthermore, another study from France confirmed an increased risk of clinical and surgical recurrence after resection in case of a positive histological margin.…”
Section: Improved Surgical Technique May Further Support the Beneficial Effects Of Surgery To Maintain Remission In CDmentioning
confidence: 99%
“…While the evidence is equivocal, it appears that overall the majority of publications favour the theory that histologically involved margins do not increase the risk of recurrence after ileocolic resection for CD (34)(35)(36). It is worth noting that the topic has continued to be investigated and some recent studies, including a meta-analysis, have again suggested that an association exists between histologically positive margins and recurrence (37,38). There still remains issues with how histological margin positivity and recurrence are reported.…”
Section: Resection Marginsmentioning
confidence: 99%
“…Histologic risk factors, including positive margins of resection, plexitis, lymphatic vessel density, and morphologic analysis of Paneth cells, may predict POR. 85,86 Finally, microbiome dysbiosis is being recognized as a risk factor with recolonization of microbiota, including Proteobacteria, Akkermansia spp., Fusobacteriaceae and a depletion of Streptococcaceae, Actinomycineae, Faecalibacterium. [35][36][37] Interestingly, active smoking was associated with elevated levels of Proteus, 37 and thus these risk factors may be interactive.…”
Section: Risk Factors and Stratification For Postoperative Recurrencementioning
confidence: 99%